Perwujudan Good Governance Pada Pelayanan Publik Melalui Aplikasi Peduli Lindungi - Surya Kurniadi (LPPM Universitas Ekasakti Padang, 2023)
The provision of public services is the state's effort to fulfill the basic needs and civil rights of every citizen regarding goods, services and administrative services provided by public service providers, so that the effectiveness of a government system is largely determined by the good and bad implementation of public services. In this case, the Preamble to the 1945 Constitution in the 4th paragraph also expressly stated that one of the objectives of the establishment of the Republic of Indonesia was to advance the welfare of society and make the nation's life intelligent. When the Covid-19 pandemic situation occurred in Indonesia, the Government made maximum efforts to overcome the spread of the Sars Covid-19 Virus through the PeduliLindung application, which is a form of the Indonesian government's response to overcome the threat of the Covid-19 pandemic. This application is a form of government presence in issuing public policies and as an instrument for tracking the spread of the Covid-19 virus in Indonesia.